MONITORING GROUNDWATER STORAGE IN NORTHERN CHILE BASED ON SATELLITE OBSERVATIONS AND DATA SIMULATION - Henry, Montecino C (Boletim de Ciências Geodésicas, 2016)
Groundwater is one of the most valuable sources of fresh water in many places worldwide, especially in regions with low pluviometric indices such as northern Chile. Thus, it is mandatory to monitor this precious resource in space and time domains. Currently, groundwater in Chile is monitored using sparse stations of water table observations. Although other indirect alternatives such as space-borne observations can contribute to regional understanding of groundwater variations, they have been poorly studied in Chile. In this study, groundwater monitoring is carried out based on 104 monthly solutions of the Gravity Recovery and Climate Experiment (GRACE) mission between 2004 and 2013. The extraction of the groundwater storage (GWS) signal obtained from GRACE was recovered once the effects of soil moisture and snow storage, retrieved from the Global Land Data Assimilation System (GLDAS), were removed. Analysis of the data was performed point-wise (six stations) and at regional scale (Northern Chile). Overall, the results are correlated with wells observations obtained by the General Directorate of Water Resources (DGA) of the Ministry of Public Works of Chile. Point-wise comparison shows root mean square error (RMSE) large than 30.0 mm while regional scale validation shows RMSE of 21.5 mm. Furthermore, regional groundwater variations obtained from GRACE/GLDAS are highly consistent in terms of trend with results obtained from well observations in the DGA network. The Empirical Orthogonal Function (EOF) analysis revealed higher annual groundwater variability in the metropolitan region and a higher inter-annual variability in the north. The methodology used may contribute to the regional study of spatial-temporal variations of groundwater in regions with sparse hydrometric network.